In silico study of biological activity of 2-[5-(furan-2-yl)-4-phenyl-4n-1,2,4-triazol-3-ylthio]-1-(4-chlorophenylethanone) - N. M. Borysenko; I. V. Bushuyeva; V. V. Parchenko; O. P. Shmatenko; А. М. Solomennyi; O. K. Yerenko; O. P. Kileyeva (Український журнал військової медицини, 2025)
Introduction. In modern conditions, where military conflicts are accompanied by significant psychological and physical stress on participants, the development of effective antiepileptic drugs has become one of the key challenges in medicine. This issue is particularly relevant due to the increasing number of cases of traumatic brain injuries, concussions, and other stress-related damages that can provoke convulsive states. In this context, derivatives of 1,2,4-triazole, which possess a broad spectrum of biological activity, including anticonvulsant effects, appear promising for the creation of new pharmaceutical agents capable of meeting the needs of military medicine.